IMPLEMENTATION OF POLITENESS-BASED LANGUAGE EDUCATION IN ELEMENTARY SCHOOL LEVEL - Novria Grahmayanuri; Linda Efrina Nasution; Shoufi Nisma Dewi; Nadrah Sitorus; Rehmenda Christy (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Verbal violence among elementary school students has become a significant issue that affects children’s psychological well-being, social relationships, and learning environment. This study aims to implement politeness-based language education as a strategy to address verbal violence in school settings. The program employed a Participatory Action Research (PAR) design involving 30 elementary school students. The intervention was conducted through interactive and participatory activities, including role-playing, guided conversations, group discussions, and educational games, over four to six sessions. Data were collected through pre-test and post-test assessments, classroom observations, questionnaires, and teacher interviews. The findings indicate a significant improvement in students’ understanding of polite language, as well as positive changes in their communication behavior. Students demonstrated an increased ability to distinguish between polite and impolite expressions and showed greater awareness of the social and emotional impact of their language use. In addition, a noticeable reduction in verbal aggression was observed during classroom interactions. The results suggest that politeness-based language education is an effective approach to fostering respectful communication and reducing verbal violence among students. The integration of cognitive, behavioral, and socio-emotional aspects in language learning contributes to the development of students’ communicative competence and character. Therefore, it is recommended that such programs be integrated into regular classroom practices and supported by continuous collaboration between schools, families, and communities to ensure sustainable outcomes.